Application Effect of External and Internal Elevation of Maxillary Sinus in Implant Restoration of Posterior Maxilla. (1st September 2022) - Deng, Xuan; Shi, Rujie; Zhan, Jia; Yang, Fang
Abstract : Objective . To explore and analyze the application effect of external and internal elevation of the maxillary sinus in implant restoration of the posterior maxilla. Methods . A total of 84 patients undergoing implant restoration of the posterior maxilla in the hospital were enrolled between January 2019 and March 2021. According to the random number table method, they were divided into the observation group ( n  = 42) and the control group ( n  = 42). The control group underwent external elevation of the maxillary sinus, while the observation group underwent internal elevation of the maxillary sinus. At 6 h, 12 h, and 24 h after surgery, the pain degree between the two groups was compared. All were followed up at 6 months after surgery. The osseointegration (bone resorption around implants, elevation height of maxillary sinus floor, average healing time) and soft tissues (bleeding index, plaque index, probing depth) in both groups were observed. The occurrence of postoperative complications was recorded. Results . At 6 h, 12 h, and 24 h after surgery, VAS scores in the observation group were significantly lower than those in the control group (P < 0.05 ). At 6 months after surgery, bone resorption and elevation height of the maxillary sinus floor in the observation group were significantly higher than those i.0.0n the control group, and the average healing time was significantly shorter than that in the control group (P < 0.05 ). The bleeding index, plaque index, and probing depth in the observation group were significantly lower than those in the control group (P < 0.05 ). There was no significant difference in the incidence of postoperative complications between the observation group and the control group (9.52% vs. 19.05%) (P > 0.05 ). Conclusion . The application effect of internal elevation of the maxillary sinus is good in implant restoration of the posterior maxilla, which can relieve pain and swelling and improve implant effect.